Siirtymiä ja ajan merkkejä koulutuksessa Opetussuunnitelmatutkimuksen näkökulmia - Autio, Tero; Hakala, Liisa; Kujala, Tiina (Tampere University Press, 2019)
This edited book continues the discussion on curriculum, which began in 2017 with the authors' previous work - the first book on Curriculum Studies in Finnish. The articles are divided into four thematic sets, the common denominator of which is the concern about the drifting of the comprehensive democratic German and Nordic Bildung/Didactic curriculum tradition into the narrower, competence and skills driven Anglo-American education and curriculum, shaped by the paradoxical alliance of assumedly apolitical instrumental learning theories and neoliberal policy measures.